A survey of current approaches to thyroid nodules and thyroid operations. (June 2018) - Isik, Arda; Firat, Deniz; Yilmaz, Ismayil; Peker, Kemal; Idiz, Oguz; Yilmaz, Bahri; Demiryilmaz, Ismail; Celebi, Fehmi
Abstract: Introduction: Thyroid nodules are commonly seen. Our aim is to learn the behaviors and operational attitudes of surgeons approaching the thyroid nodules. In a literature search, our study is the first and only study performed merely on surgeons. Materials- Metods: This cross-sectional study was done between June 2014–January 2015. The questionnaire consists of 25 questions. Initially, general questions consisting of demographic findings were asked. In step 2, questions consisting of the index case and case variants were asked. Results were compared with American Thyroid Association, European Thyroid Association guidelines, and Australia survey results. In the last step, questions about thyroid operations were asked. Results: A total of 301 surgeons responded to the survey. The response rate was approximately 20%. Thirty nine were female and 262 were male. For the question that asks the diameter of the thyroid nodule that will require a thyroid fine needle aspiration biopsy (TFNAB), 47.5% of the surgeons will require a TFNAB for 1–2 cm solid nodules. 40.15% of the surgeons required a TFNAB regardless of size. 46.1% of the surgeons who required a TFNAB between 1 and 2 cm solid nodules also required scintigraphy at diagnosis of suppressed TSH case variant. Conclusion: In this survey, we identified differences from up-to-date guidelines about approaching thyroid nodules and perioperative thyroid surgery. From our perspective, surgeons need updated training requirements. This can be done with updated seminars across the country. Thereby approaches may become standard and consequently patients may have qualified services. Highlights: The purpose of the present study is to learn the behaviors and operational attitudes of surgeons approaching the thyroid nodules. In a literature search, our study is the first and only study performed merely on surgeons. Present study will have contribution to ATA and ETA guidelines.